Implementation of a Teacher Development Website with Waterfall Development to Support the Teacher Promotion Process at SMP 2 Jekulo Kudus - Ahmad Fahruddin; Endang Supriyati; Tri Listyorini (Journal of Innovation and Technology Polbeng Series on Informatics (INOVTEK Polbeng - Seri Informatika), 2025)
This website is designed to support the promotion process of teachers at SMP 2 Jekulo Kudus by utilising digital technology. The main objective of this development platform is to improve the efficiency and quality of the management of teacher professional development programs. The problem to be overcome is the slow process of submitting promotion files which are often unstructured, thus hampering teacher career development. This platform provides a document management feature that makes it easier for users to submit promotion files. With this feature, teachers can upload the required documents, unify the application status in real time, and receive notifications regarding their application process. This not only speeds up the process but also reduces the possibility of loss or error in document management. The specific impact of implementing this website on the teacher promotion process includes increasing transparency and accountability in applying for promotions. With a structured system, teachers can more easily meet the requirements set, contributing to their increased professionalism. The use of MySQL as a database also ensures that data is managed quickly and efficiently. Overall, this website is expected to be an effective digital solution in supporting the teacher promotion process while improving the quality of education at SMP 2 Jekulo Kudus.